Herpes simplex Virus Pneumonitis in an Acute/Subacute Paracoccidioidomycosis Patient With Malabsorption Syndrome. Case-Report and Literature Review - Cavalcante, Ricardo S.; Souza, Bruno S.; Duarte, Iverson X.; Moraes, Marcelo P. T.; Coelho, Kunie I. R.; Griva, Beatriz L.; Pereira, Beatriz A. S.; Calvi, Sueli A.; Betini, Marluci; Mendes, Rinaldo P. (Frontiers in Fungal Biology, 2022)
Paracoccidioides sp – Herpes simplex virus co-infection was not reported until now and malabsorption syndrome is a rare complication of the acute/subacute form of paracoccidioidomycosis (PCM), characterized by life-threatening abnormalities – fat and protein loss, lymphopenia, ascites and intense immunosuppression. A 21-year old woman presented the PCM acute/subacute form with intense involvement of the abdominal and intestinal lymphoid organs, which leads to the malabsorption syndrome and severe immunosuppression. This patient developed a fatal-disseminated Herpes simplex virus (HSV) infection associated with the paracoccidioidal disease. This case demonstrates that, in addition to the antigen-specific immunosuppression, some PCM patients can present a generalized cell-mediated immune depression and endogenous infection of latent microorganisms. On the best of our knowledge, this is the first report of association between PCM and HSV infection.